1994
DOI: 10.1097/00000658-199410000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nissen Fundoplication Is an Effective Treatment for Gastroesophageal Reflux Disease

Abstract: ObjectiveThe open Nissen fundoplication is effective therapy for gastroesophageal reflux disease. In this study, the outcomes in 198 patients treated with the laparoscopic Nissen fundoplication was evaluated for up to 32 months after surgery to ascertain whether similar positive results could be obtained. Summary Background DataTo ensure surgical success, patients were required to have mechanically defective sphincters on manometry and increased esophageal acid exposure on 24-hour pH monitoring. The patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
229
0
27

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(267 citation statements)
references
References 12 publications
11
229
0
27
Order By: Relevance
“…The study population consisted of patients with advanced stages of chronic GERD who are typically referred for surgery [10,29,30]. The patients had suffered from the disease for more than 10 years and had continuous daily PPI therapy for more than 6 years before undergoing the TIF procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population consisted of patients with advanced stages of chronic GERD who are typically referred for surgery [10,29,30]. The patients had suffered from the disease for more than 10 years and had continuous daily PPI therapy for more than 6 years before undergoing the TIF procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients (n = 14, 50% female) available at 2 years had a median age of 34 (range, 23-55) years and a median BMI of 22 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) kg/m 2 . Patients had suffered from GERD for a median of 10 (range, 3-15) years and were on continuous daily PPI therapy for a median of 6 (range, 2-13) years before undergoing TIF.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Furthermore, new technical details such as new instruments for a new surgery, learning curve on this new surgical practice, technical diffi culties for the division of the SGV have been discussed. Some publications relating important and long-lasting dysphagia with the non-liberation of the gastric fundus through SGV division 9,22,23 . New techniques were described, as the fundoplication without SGV division to prevent such complication 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Dallemagne described and reported the results of laparoscopic Nissen fundoplication (Dallemagne et al, 1991). Since then, several studies have demonstrated the safety and efficacy of laparoscopic fundoplication (Hallerbäck et al, 1994;Hinder et al, 1994;Hunter et al, 1996;Jamieson et al, 1994;Watson et al, 1996) (Table 3). …”
Section: Laparoscopic Anti-reflux Operationsmentioning
confidence: 99%